CFD Analysis on the Performance of Twisted Tapes in Horizontal Heat Exchangers for Shower Water Heat Recovery - Eduardo Silva; Vitor Ferreira; José Cunha; Eliseu Monteiro (Journal of Heat and Mass Transfer Research)
The thermal energy found in shower hot wastewater, which is usually dumped, can be recovered through heat exchangers and used to pre-heat shower cold-water, contributing to energy sustainability. The objective and novelty of this work are to present a computational fluid dynamics (CFD) model and a theoretical model based on literature correlations to evaluate the performance of a shower water horizontal heat exchanger with twisted tape inserts. CFD simulations are used to improve the shape of twisted tape in the setting of the turbulator. The findings suggest that the wastewater flow convection heat transfer coefficient is between the flow around a cylinder and the flow around a cylinder in a narrow channel. The results for the turbulator are consistent with theoretical data, except for twist ratios below 3. The most promising twisted tape design has a twist ratio of 4 and a thickness of 1 mm. A conclusion could be drawn that the efficacy of the twisted tape in the heat exchanger is greater at lower flow rates. The performance gain ranges from 18.1 % to 3.0 % for flow rates of 3–10 L/min. Future directions for this research should focus on the improvement of the external convection coefficient because it represents the highest thermal resistance in the shower wastewater horizontal heat exchanger.